The Influence of the Pandemic on Decisions Occuring During the Last Few Years - Jarrett, Jeffrey E. (Advances in Social Sciences Research Journal, 2023)
The notion that present value of cash flows is often improperly estimated in financial models concerning capital improvements and abandonments is a fundamental problem in decision analysis in management and associated decisions and affects estimation of and valuation of intellectual property. Previous studies indicate the usefulness of estimation theory in financial in financial accounting. During the Covid Pandemic of the past few years decisions by governmental and health authorities in the United States and the World were often dictatated during the Pandemic by short-term political influences which included disinformation by some who wished to rake advantage of the misuse of the health Pandemic for political gain and/or financial power and short-term financial gain. Previously this was show to be true as the media with the aid of self-promotional activities by many who were attempting this kind of gain. Furthermore the Pandemic in the United States and other nations is receding in drfamatic ways and many restrictions of the Endemic era are nolonger in use. This was the result of Mask restrictions and increasing but not universal vaccine programs many states and nations.